ANALISIS RISIKO BANK TERHADAP TINDAKAN CYBER FRAUD PADA PT BANK CENTRAL ASIA - Afifah Khairunnisa (2023)
The purpose of writing this thesis is to analyze bank risks arising from cyber fraud on behalf of PT Bank Central Asia. The writing method in this Final Project is to use data collection techniques by conducting interviews with the management of PT Bank Central Asia as well as qualitative descriptive analysis to understand phenomena related to the object of writing such as perceptions, opinions, views, actions, and others. The result of this final project report is that there are 3 operational risks, 2 reputational risks, and 1 strategic risk due to cyber fraud. The risk management process begins with risk identification, risk assessment, risk matrix, risk response and risk control. The conclusion obtained is that there is an operational risk of theft of customers' personal data by hackers from phishing links with a risk score of 12, entering the category of moderate level, the response carried out is that the risk can be accepted only with very good control, the control carried out is PT Bank Central Asia provides education to its customers, both directly and indirectly, not to trust non-official sites on behalf of PT Bank Central Asia.